Rational Emotive Behavior Therapy (REBT) Dalam Konseling Kelompok: Menantang Keyakinan Irasional - Amirah, Nadiratul; Karneli, Yeni; N, Netrawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Rational Emotive Behavior Therapy (REBT) is one of the counseling approaches developed by Albert Ellis. This approach emphasizes the importance of challenging and changing irrational beliefs that are the root of an individual’s emotional and behavioral problems. In the context of group counseling, REBT has great potential in building supportive group dynamics, identifying irrational thoughts, and facilitating the process of cognitive and emotional change. Through group counseling, individuals gain interpersonal support that allows for the process of collective belief disputation, strengthening rationality and increasing self-efficacy. The ABCDE model as the main framework in the REBT counseling process, accompanied by techniques such as role playing, imagery and the use of humor to facilitate cognitive change. Therefore, this article comprehensively discusses the application of REBT in group counseling, focuses on challenging irrational beliefs, and examines its effectiveness based on the findings of various national and international studies.